Efecto de productos químicos sobre el control de sogata (tagosodes orizicolus) en la zona de Montalvo en el recinto San Joaquín - Calero Alarcón, José Luis (2017)
SUMMARY The present experimental work was carried out at the premises of luis calero alarcón, located at km 26 ½ on the montalvo road, between the geographic coordinates 1 ° 49'17.0 latitude south and 79 ° 27'43.5 latitude west. the height is 15 msnm, average annual temperature of 24.2 ° c; annual rainfall of 1987.4 mm, and relative humidity of 85%. certified seed of rice variety iniap 14 was used, whose treatments were conformed by sulfur, fipronil, imidacloprid, lambdacialotrina, silicio, metomyl and witness. Sulfur was applied at doses of 3000 cc / ha, fipronil at doses of 400cc / ha, imidacloprid 400 cc / ha, lambdacialotrin 300 cc / ha, silicon 3000 cc / ha, metomyl 200 gr / ha and witness. the experimental design bloques al azar, with seven treatments and four replications, was used two treatments applications, at 14 days and 28 days after sowing. All the agricultural work required for the good development of the crop, such as soil preparation, planting, irrigation, weed control, fertilization, disease control and pest and crop were carried out. during the development of the experiment, the following data were evaluated: population of nymphs and adults of tagosodes orizicolus, mechanical damage, incidence of leaf blight virus, incidence of cloud and number of tillers, ear length, yield / ha and analysis economic. the results obtained include: the most effective products for the control of tagosodes orizicolus, both as nymphs and adults were metomyl and lambdacialotrin, in their order. the best adult controls of tagosodes orizicolus were achieved 7 days after the first application and 24 hours after the second application. the best controls of nymphs were achieved 24 hours after the first application and 14 days after the second application. mechanical damage was observed in all treatments from 14 days to 56 days after sowing. the lowest percentage of mechanical damage was observed in the silicon treatment. the lowest percentage of white leaf virus attack was observed in the treatments with lambdacialotrina, silicio and metomyl. the highest yield and net profit was achieved with the treatment with silicon, with 5,776.07 kg / ha and $ 933 / ha respectively